Position statement: linear prurigo is a subtype of chronic prurigo - Pereira, Manuel P.; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2019)
Background Chronic prurigo (CPG) is a distinct disease characterized by chronic pruritus, history and/or signs of prolonged scratching and multiple pruriginous lesions. It may present with various clinical manifestations, including papules, nodules, plaques or umbilicated lesions. Some patients with chronic pruritus show pruriginous linear and scaring scratch lesions (LSSL) and it is unclear whether these lesions belong to the spectrum of CPG. Objective To achieve a consensus on the classification of pruriginous LSSL and establish criteria to differentiate them from similar appearing conditions of different nature. Methods Members of the Task Force Pruritus (TFP) of the European Academy of Dermatology and Venereology participated in the consensus conference, discussing representative clinical cases. Using the Delphi method, consensus was reached when ≥75% of members agreed on a statement. Results Twenty-one members of the TFP with voting rights participated in the meeting. It was consented that LSSL occurs due to chronic pruritus and prolonged scratching, and share common pathophysiological mechanisms with CPG. LSSL were thus considered as belonging to the spectrum of CPG and the term ‘linear prurigo’ was chosen to describe this manifestation. Conclusion Considering linear prurigo as belonging to the spectrum of CPG has important clinical implications, since both the diagnostic and therapeutic approach of these patients should be performed as recommended for CPG. Importantly, linear prurigo should be differentiated from self-inflicted skin lesions as factitious disorders or skin picking syndromes. In the latter, artificial manipulation rather than pruritus itself leads to the development of cutaneous lesions, which can show clinical similarities to linear prurigo